1998
DOI: 10.1046/j.1529-8817.1998.340009.x
|View full text |Cite
|
Sign up to set email alerts
|

Minireview—the First Kiss: Establishment and Control of Initial Adhesion by Raphid Diatoms

Abstract: Minireviews do not have abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 223 publications
(166 citation statements)
references
References 18 publications
5
152
0
2
Order By: Relevance
“…Decho 1990;Hoagland et al 1993;Costerton et al 1995;Gosselin et al 1997) in the aquatic environment. The EPS are composed of several mucoid substances which aid, e.g., in cell locomotion (Wetherbee et al 1998) and adhesion to surfaces (Cooksey and WigglesworthCooksey 1995). In addition to direct biological functions EPS enhance the agglutination of planktonic organic and inorganic particles (Hamm 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Decho 1990;Hoagland et al 1993;Costerton et al 1995;Gosselin et al 1997) in the aquatic environment. The EPS are composed of several mucoid substances which aid, e.g., in cell locomotion (Wetherbee et al 1998) and adhesion to surfaces (Cooksey and WigglesworthCooksey 1995). In addition to direct biological functions EPS enhance the agglutination of planktonic organic and inorganic particles (Hamm 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Once individual diatoms reach a surface, adhesion, movement, and release are active processes (Cooksey and Wigglesworth-Cooksey 1995;Wetherbee et al 1998) that could allow substrate selection. Studies using marine diatoms have demonstrated responses to physical and chemical cues (Wigglesworth-Cooksey and Cooksey 1992;Falciatore et al 2000;Thompson et al 2008) and such cues may be involved in diatom colonization.…”
Section: Discussionmentioning
confidence: 99%
“…As espécies encontradas sobre o molusco possuem rafe, pela qual eliminam ao exterior mucilagem, que é composta predominantemente por polissacarídeos (Wetherbee & Burke 1998). Esse biocomponente possibilita a aderência das diatomáceas ao substrato e esta fixação pode se dar de várias formas: pela adsorção de toda a face valvar com rafe (forma adnata), caso do gênero Cocconeis; pela formação de pedúnculos, caso de Gomphonema e Encyonema; ou pela formação de uma matriz produzida pelos primeiros colonizadores, que adere os organismos da sucessão, caso dos demais gêneros (Barber & Haworth 1994 …”
Section: Discussionunclassified